Preparation of a highly efficient Pt/USY catalyst for hydrogenation and selective ring-opening reaction of tetralin - Qi Wang (KeAi Communications Co., Ltd., 2018)
Abstract Ultrastable Y zeolite (USY)-supported Pt catalyst was prepared by gas-bubbling-assisted membrane reduction. The influence of reaction conditions and the metal and acid sites of catalysts on the catalytic performance of catalyst in hydrogenation and selective ring opening of tetralin, 1,2,3,4-tetrahydronaphthalene (THN), was studied. It was found that the optimal reaction conditions were at a temperature of 280 °C, hydrogen pressure of 4 MPa, liquid hourly space velocity of 2 h−1 and H2/THN ratio of 750. Under these optimal conditions, a high conversion of almost 100% was achieved on the 0.3Pt/USY catalyst. XRD patterns and TEM images revealed that Pt particles were highly dispersed on the USY, favorable to the hydrogenation reaction of tetralin. Ammonia temperature-programmed desorption and Py-IR results indicated that the introduction of Pt can reduce the acid sites of USY, particularly the strong acid sites of USY. Thus, the hydrocracking reaction can be suppressed.